Answer:
9.405
Step-by-step explanation:
Answer:
f(x) = 2x^2 - 3x + 1
Step-by-step explanation:
The root 1 is associated with the factor (x - 1).
The root 1/2 is associated with the factor (x - 1/2), which in turn is equivalent to (2x -1)
The quadratic in question is f(x) = (x - 1)(2x - 1). To write this in standard form, perform the indicated multiplication:
f(x) = 2x^2 - 2x - x + 1, or f(x) = 2x^2 - 3x + 1
Hey there Mejia021274,
1) Independent systems have exactly one solution:
x + y = 1
x - y = 3
x = 2, y = -1
2) Inconsistent systems have no solutions :
5x + y = 6
5x + y = 10
There is no solution as 5x + y cannot be equal to 6 and 10
3) Consistent systems have a lot of solutions:
x+y = 5
<span>2x+2y = 10 </span>
<span>A few solutions to this system are (1,4), (2,3), (3,2), (4,1), (5,0), and so on.
</span>
Hope this helps :))
~Top
Answer:A
=
a
+
b
2
h
Step-by-step explanation:
Answer:
dnsjsjdkdksldnd xidjdbdksksjdkdnjddj